Da tolerância à hospitalidade na democracia por vir. Um ensaio a partir do pensamento de Jacques Derrida - Pereira, Gustavo Oliveira de Lima (2014)
The main objective of this thesis focuses on articulate, primarily from the thought of Jacques Derrida, an alternative course to think about ethics, politics and democracy at present times, taking as the starting point the category of "hospitality", a philosophical adventure that can be understood as another name of deconstruction and, a central concept in the thinking of the Algerian-French philosopher. Therefore, it refutes the category of "tolerance", idea that synthesizes, in general, the tradition of thinkers identified with the Enlightenment heritage, both in Modern as Contemporary Philosophy, and it still proclaims itself as the last step of History, in the context of human relationships and among States. Thus, the hospitality, accordingly to Derrida, would be the enough powerful category to redirect the discussion of freedom, politics and democracy (and all the other circumstances that slides to those categories) to the dimension of the to come and so, for the reinsertion of temporality as a philosophical element that rebels to beyond the domestication enforced by the desire to control, summed up in the idea of desire for sovereignty. In this thesis, sovereignty will be designed both on the dimension of intersubjective relationship as the "desire for appropriation" employed by the ipseity of the same on an otherness, seen in the relationship between the host and the guest (whether as a foreigner, a rougue or of ghost) - as in the political context (in the strict sense), where the concept of sovereignty (expressed under the control of tolerance) acts from the authority of Law, the boundaries between States, the nationality, and the homeland at last, under the level of predictability and calculability. The aporia established between the hospitality Law and the laws of hospitality, developed by Derrida, leads the thought of the sovereignty deconstruction to an opening capable of enabling the reinvention of a left wing political thought, silently waiting in the event of the democracy to come.